2016
DOI: 10.12705/654.1
|View full text |Cite
|
Sign up to set email alerts
|

Shedding new light on old algae: Matching names and sequences in the brown algal genus Lobophora (Dictyotales, Phaeophyceae)

Abstract: The existence of massive cryptic diversity in algae makes linking DNA‐based lineages to existing taxa exceedingly difficult. A better integration of historical collections into modern taxonomic research is therefore highly desirable. Using the brown algal genus Lobophora as a test case, we explore the feasibility of linking taxonomic names to clades in modern phylogenies. Despite Lobophora being a pantropical genus with probably more than 100 species, traditionally only a handful of species have been recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
138
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(148 citation statements)
references
References 43 publications
(61 reference statements)
8
138
1
1
Order By: Relevance
“…Some of the specimens used to describe new Lobophora species in this study (= LAF samples) were previously included in other Lobophora investigations (see Vieira et al. , ; Table in the Supporting Information). Collections were made from diverse habitats and from the intertidal to 90 m depths across different seasons, using snorkeling, SCUBA diving or by vessel‐deployed Hourglass‐design box dredging (Joyce and Williams , Felder et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the specimens used to describe new Lobophora species in this study (= LAF samples) were previously included in other Lobophora investigations (see Vieira et al. , ; Table in the Supporting Information). Collections were made from diverse habitats and from the intertidal to 90 m depths across different seasons, using snorkeling, SCUBA diving or by vessel‐deployed Hourglass‐design box dredging (Joyce and Williams , Felder et al.…”
Section: Methodsmentioning
confidence: 99%
“…For example, an undescribed species has been reported growing epiphytically on the prop roots of red mangroves in Belize (Coen and Tanner ), and L. variegata has also been found growing on Thalassia testudinum leaves in the Florida Keys (Vieira et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular systematic studies of specimens assumed to be a broadly defined "Lobophora variegata" (Sun et al, 2012;Vieira et al, 2014Vieira et al, , 2016Schultz et al, 2015) have revealed numerous new species that were previously misidentified or unrecognized. The species L. variegata is likely restricted to the Caribbean Sea (Schultz et al, 2015;Vieira et al, 2016).…”
Section: Remarksmentioning
confidence: 99%
“…The species L. variegata is likely restricted to the Caribbean Sea (Schultz et al, 2015;Vieira et al, 2016). Vieira et al (2016Vieira et al ( , 2017) estimated there are more than 100 species of Lobophora, of which only 21−30 species are currently recognized. The Gulf of California specimens referred to "L. variegata" should be critically studied and molecularly compared to determine their correct identity and if there is possibly more than one species in the Gulf.…”
Section: Remarksmentioning
confidence: 99%